Penerapan Media Torso Dalam Pembelajaran IPA SD Untuk Meningkatkan Keterampilan Observasi Siswa Di SDN Bangkal II - Ach Syamsul Muarifillah; Oneil Izzat Zakaria; Sofyan Pratama M (LPPM Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Bojonegoro, 2025)
Natural Sciences (IPA) plays a crucial role in understanding the universe through precise observation and systematic procedures. It is crucial that science material be delivered to students appropriately to achieve learning objectives. This study aims to determine the level of students' observation skills in Natural Sciences learning using torso media. The results showed that students were very enthusiastic and enthusiastic in the science learning activities using torso media. Students demonstrated their curiosity by asking several questions to the teacher. This proves that the use of torso media in Natural Sciences learning can improve students' observation skills. Therefore, the use of media in learning must be appropriate. This is because the use of media is one of the factors that contribute to the achievement of learning outcomes.